Influência do protocolo restaurador no comportamento biomecânico em dentes pré-molares com lesões cervicais não cariosas e cavidades MOD - Pires, Mariana Fernandes (2023)
This study aimed to evaluate the residual shrinkage stress (ShrS), displacement of cusps (DC), and cuspal strain (CS) generated by the polymerization of composite resin restorations of premolar teeth with non-carious cervical lesions (NCCLs) and mesio-occlusal-distal (MOD) cavities. The biomechanical behavior of the teeth was analyzed comparatively between different methodologies: 1) computational simulation of stress distribution by finite elements analysis (FEA); 2) analysis of cuspal strain by strain gauge testing. The FEA simulated ShrS using modified von Mises criteria according to the cavity that would be restored first (restorative sequence) and the MOD restorative protocol (incremental technique and Bulk fill technique) divided into four groups (G1-G4): G1- 1 st NCCL and 2nd MOD incremental; G2- 1 st NCCL and 2nd MOD Bulk fill; G3- 1 st MOD incremental and 2nd NCCL; G4- 1 st MOD Bulk fill and 2nd NCCL. For the strain gauge test, forty human maxillary premolars were collected and divided into groups (n =10). Two gauges were bonded to each specimen to measure CS during the restorative procedure, and the wires were connected to the Data Acquisition System (ADS2000, Lynx). Cuspal strain values (buccal and palatal) were submitted to statistical analysis (ANOVA). The incremental technique groups indicated higher ShrS, DC, and CS values, regardless of the restoration sequence. The restorative sequence did not affect the ShrS and CS, but restoring NCCL before the MOD cavity resulted in lower stress peaks during the procedure and DC.